QUALITY CONTROL OF SANDWICH PANEL PRODUCTS USING SEVEN TOOLS AND SIX SIGMA METHODS - Herlyana Putra Azizul Hakim; Wiwik Sulistiyowati (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: The purpose of this research is to identify product defect factors and provide technical recommendations to improve quality. Method: The methods used are Seven Tools and Six Sigma to identify and evaluate potential failures at PT XYZ. The Seven Tools method by applying improvement steps and analyzing the types of defects with the Six Sigma method. Results: The results showed that the factors causing product defects that can be seen from the fishbone diagram are known, namely, humans, machines, materials, and methods and provide suggestions for improvements that are applied to minimize the occurrence of defects. After the corrective action taken, it was able to minimize the number of defects by 5%. Novelty: PT XYZ is a company engaged in manufacturing that produces sandwich panels. The problem faced by this company is the large number of product defects during the production process in the October-December 2023 period amounting to 10% of total production.